i-Motif of cytosine-rich human telomere DNA fragments containing natural base lesions - Dvoráková, Zuzana; Renciuk, Daniel; Kejnovská, Iva; Školáková, Petra; Bednárová, Klára; Sagi, Janos; Vorlícková, Michaela (Nucleic acids research, 2018)
i-Motif (iM) is a four stranded DNA structure formed by cytosine-rich sequences, which are often present in functionally important parts of the genome such as promoters of genes and telomeres. Using electronic circular dichroism and UV absorption spectroscopies and electrophoretic methods, we examined the effect of four naturally occurring DNA base lesions on the folding and stability of the iM formed by the human telomere DNA sequence (C3TAA)3C3T. The results demonstrate that the TAA loop lesions, the apurinic site and 8-oxoadenine substituting for adenine, and the 5-hydroxymethyluracil substituting for thymine only marginally disturb the formation of iM. The presence of uracil, which is formed by enzymatic or spontaneous deamination of cytosine, shifts iM formation towards substantially more acidic pH values and simultaneously distinctly reduces iM stability. This effect depends on the position of the damage sites in the sequence. The results have enabled us to formulate additional rules for iM formation.
Keywords: Cytosine; pentoxyl; DNA; Adenine; adenin; poškození DNA; uracil; Pentoxyl; Uracil; lidé; DNA Damage; cytosin; Humans; telomery; Telomere